A debris layer evolution-based model for predicting both fretting wear and fretting fatigue lifetime. (January 2021) - Shen, Fei; Ke, Liao-Liang; Zhou, Kun
Highlights: A CDM-based approach incorporating debris layer evolution is developed. The approach is implemented in finite element analysis of fretting fatigue. The wear profile, debris layer and fretting fatigue lifetime are predicted. The effects of debris layer on the prediction results are evaluated. Abstract: A continuum damage mechanics (CDM)-based approach is proposed to investigate fretting wear and fretting fatigue behavior of Ti-6Al-4V with the consideration of debris layer evolution. An elastic-plastic-damage model is developed to calculate the stress, strain, and fatigue damage fields. The debris layer and its thickness evolution are considered in a friction energy-based wear model. Both models are implemented in a finite element package to predict the fretting wear profile and fatigue lifetime. It is found that the numerical approach with the consideration of debris layer provides more accurate predictions than that without debris layer. The effects of debris layer evolution on the fretting fatigue lifetime, wear profile, contact pressure and subsurface stress are evaluated.